The Effect of Customer Engagement and Social Media Marketing on Brand Loyalty on Shopee Application User - Setyo Febri Laksmana Putra; Rizky Dermawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Competition between marketplaces is competing to provide the best platform for online shopping. Therefore, companies need to pay attention to variable such as consumer engagement and social media marketing which attract users and influence customer loyalty so that they continue to be loyal to use their platform. his study aims to investigate the influence of consumer engagement and social media marketing on brand loyalty among Shopee app users in Surabaya. This research was conducted using a quantitative approach and involved 96 respondents as the sample. The sample was selected using purposive sampling method with snowball sampling approach. The data used consisted of primary data and secondary data. The analysis method applied is component-based structural equation modeling (SEM), using the partial least square (PLS) analysis tool with validity test, reliability test and hypothesis testing.The results of this study prove that: (1) Customer Engagement has a positive and significant effect on Brand Loyalty. (2) Social Media Marketing has a positive and significant effect on Brand Loyalty.